Bram Stoker's notes for Dracula a facsimile edition - Stoker, Bram 1847-1912 (McFarland, 2008)
"Bram Stoker's initial notes and outlines for his landmark horror novel Dracula were auctioned at Sotheby's in London in 1913 and eventually made their way to the Rosenbach Museum and Library, where they are housed today. This comprehensive work reproduces the handwritten notes both in facsimile and in annotated transcription. It also includes Stoker's typewritten research notes"--Provided by publisher.